(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Teenage pregnancy is coming up as one of the most important social and public health problem in both developed and developing countries and has an increased risk of both maternal and fetal complications specially in developing countries like Bangladesh. The purpose of the study to determine the fetal and maternal outcomes of teenage mother in Chittagong Medical College Hospital (CMCH) Materials and methods: A cross-sectional observational study was conducted at the Obstetrics and Gynaecology Department of Chittagong Medical College Hospital for a period of six months from 10th October 2013 to 9th April 2014. One hundred teenage mothers (Aged 15-19 completed years at delivery) who got herself admitted to the Department of Obstetrics and Gynaecology were included in this study. Diagnosis was established by history, presenting complaints, physical examination, per-abdominal examination and per-vaginal examination who required. Complications during pregnancy and labour, postpartum complications and perinatal outcome were noted. Data were analyzed by SPSS-18. Results: During this study period, 60% mothers were in age group of 17-18 years. Most of the patients were primigravida (72%). Majority (56%) of patients were in no antenatal cheek up. Most of patients (75%) admitted at her gestational age (37 – 42 wk). Among them, maximum patients (44%) were delivered by caesarean section. Most of teenage mothers (64%) were suffered from various complications during pregnancy and labour like preterm labour (21.87%), prolonged labour (17.18%), anaemia (14.06%), obstructed labour (12.50%), gestational hypertension (7.81%), Urinary tract infection (7.81%), pre-eclampsia (4.68%) eclampsia (3.13%). 57%of teenage mothers suffered from postpartum complications including post-partum hemorrhage (21.05%), anaemia (17.54%), inadequate lactation (14.03%), postpartum eclampsia (10.53%), wound infection (10.53%), puerperal sepsis (5.26%), urinary tract infection (3.51%) and puerperal psychosis (3.51%). About 15% mothers delivered low birth weight babies, 93% of those were premature. 48% of babies were suffered from various complications. Among them, prematurity (29.17%), birth asphyxia (25%), neonatal jaundice (25%), sepsis (12.50%), congenital heart disease (4.17%), congenital anomalies (2.08%) and intra-uterine growth restriction (2.08% were common.43% babies needed hospital admission due to causes of birth asphyxia (27.90%), prematurity (25.58%), neonatal jaundice (23.25%), sepsis (13.95%), congenital heart disease (4.65%).Perinatal outcomes of teenage pregnancy was alive with resuscitation 38%, alive without resuscitation 54%, intra-uterine death 1%, stillbirth 2% and neonatal death 5%. Conclusion: Teenage means the youth of the population who are the future of the nation. So, more emphasis should be given on further reduction of teenage pregnancy Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 56-60